Mapping the Shadow Banking System Through a Global Flow of Funds Analysis. (Washington, D.C. : International Monetary Fund, 2014)
This paper presents an approach to understanding the shadow banking system in the United States using a new Global Flow of Funds (GFF) conceptual framework developed by the IMF's Statistics Department (STA). The GFF uses external stock and flow matrices to map claims between sector-location pairs. Our findings highlight the large positions and gross flows of the U.S. banking sector (ODCs) and its interconnectedness with the banking sectors in the Euro area and the United Kingdom. European counterparties are large holders of U.S. other financial corporations (OFCs) debt securities. We explore the relationship between credit to domestic entities and the growth of non-core liabilities. We find that external debt liabilities of the financial sector are procyclical and are closely aligned with domestic credit growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet